Calculation of Financial Ratios on PT ACE Hardware Indonesia Tbk - Jessica Gabrella Kuhon; Nanik Lestari (Pusat P2M Politeknik Negeri Batam, 2016)
The purpose of this research was to find out how the development ratio of liquidity, solvency and profitability at PT ACE Hardware Indonesia Tbk. Data used are descriptive data in the form of financial statements, financial position report, income statement, and cash flow statement PT ACE Hardware Indonesia Tbk 2009-2014 period obtained from Indonesia stock exchange official website